Development of Web-Based Learning Application for Generation Z - Bambang Hariadi; M.J. Dewiyani Sunarto; Pantjawati Sudarmaningtyas (International Journal of Evaluation and Research in Education (IJERE), 2016)
This study aims to develop a web-based learning application as a form of learning revolution. The form of learning revolution includes the provision of unlimited teaching materials, real time class organization, and is not limited by time or place. The implementation of this application is in the form of hybrid learning by using Google Apps for Education (GAfE), called Brilian. Steps being taken in the study are: (1) requirements analysis, (2) interface design, (3) construction performance, and (4) testing and implementation. The subjects of this study were students of class 2014 and course lecturers for the student of class 2014. After the system testing that was conducted in the second semester of 2014, the collected data suggest that out of 1153 students who used this application, 79% of them were comfortable in using it. As for the lecturers, the data was obtained from 70 lecturers, 82% of them stated that this application helped their teaching process. From the evaluation results, it requires universities to further improve the network infrastructure, and applications must be developed to be more user friendly, including access to mobile learning.